2016
DOI: 10.1016/j.comcom.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

MAC-aware routing metrics for the internet of things

Abstract: Wireless medium access control (MAC) and routing protocols are fundamental building blocks of the Internet of Things (IoT). As new IoT networking standards are being proposed and different existing solutions patched, evaluating the end-toend performance of the network becomes challenging. Specific solutions designed to be beneficial, when stacked may have detrimental effects on the overall network performance. In this paper, an analysis of MAC and routing protocols for IoT is provided with focus on the IEEE 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…To address this problem, headof-line delays can be used to act as the link weights instead of queue lengths [95], [96]. For a multihop network with a contention-based MAC protocol, [97] develops a new metric, called Q-metric, to jointly optimize the routing and MAC layer parameters with the objective of optimizing the energy-delay trade-off.…”
Section: Routing Layer Techniquesmentioning
confidence: 99%
“…To address this problem, headof-line delays can be used to act as the link weights instead of queue lengths [95], [96]. For a multihop network with a contention-based MAC protocol, [97] develops a new metric, called Q-metric, to jointly optimize the routing and MAC layer parameters with the objective of optimizing the energy-delay trade-off.…”
Section: Routing Layer Techniquesmentioning
confidence: 99%
“…It extends the ETX metric by considering the packet loss which may be generated by the MAC contention. The authors of [33] conducted a simulation and demonstrated that the reliability metric is better than the ETX metric. The author of [34] addressed traditional routing protocols for Adhoc networks such as AODV, DSR, and OLSR [35] and discussed their performance in an IoT environment.…”
Section: Iot Routing Protocolsmentioning
confidence: 99%
“…The simulation results show that CASCR has low energy consumption. The authors of [33] involved in developing a cross-layer protocol to meet the performance parameters of IoT applications: minimum date delivery rate, and maximum packet delay. The proposed protocol runs on the top of IEEE 802.15.4.…”
Section: Iot Routing Protocolsmentioning
confidence: 99%
“…Numerous devices in MAC and other protocols are industrialized to ensure the function of WN. Marco et al [29] has defined MAC as well as forwarding rules to IoT that was given using the objective on the IEEE 802.15.4 MAC as well as IETF RPL procedures. The routing parameters and MAC parameters are permitted in the projected system to upsurge the performance.…”
Section: Related Workmentioning
confidence: 99%
“…Under such instance, proper scheduling of energy utilization is required especially when the sensors are distantly connected [16][17]. Numerous nodes transfer multiple data from node to the base station about the same event, which leads to transfer redundant data [18][19]. Thus, the consumption of energy associated with the network become high.…”
Section: Introductionmentioning
confidence: 99%